Gender Equity in Indonesian Higher Education: Exploring the Opportunities of Women's College Graduates as University Leaders - Zaenal Mustakim (Muwazah, 2021)
Gender equity is an important target in human development, both at the national and global levels. Gender equity in the higher education context is a crucial issue. This study was aimed at analyzing the gender-based differences in Indonesian higher education graduates. Further, this study also explored the opportunity for women to become university leaders. In this study, a quantitative method was employed by using one-way analysis of variance (ANOVA) to analyze the gender gap in higher education. This study involved the secondary data taken from the Ministry of Research, Technology, and Higher Education (Kemenristekdikti) in the year 2019. This study revealed that there is no significant difference between men and women graduates from higher education. However, the descriptive data indicates that the number of women graduates is higher than men graduate. Further, the findings of this study also show that the opportunity for women’s college graduates to become university leaders is widely opened, but commonly they find various obstacles in the field.